IMPROVEMENT OF LEGAL REGULATION OF CONTROL AND MONITORING IN THE FIELD OF PUBLIC PROCUREMENT - Polishchuk, Inna; Steshenko, Diana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to study and analyze the main problems of the current state of legal regulation of control and monitoring in the field of public procurement, as well as the development of scientifically based proposals for improving legal control and monitoring mechanisms capable of promptly responding to violations in this area for the transparent, effective and rational use of budget funds. Research methods: the methodological basis of the study consisted of general scientific and special legal methods of cognition of phenomena and processes, in particular analysis, synthesis, deduction, systemic-structural, logical-legal and comparative-legal methods, which made it possible to comprehensively analyse the legal regulation of control and monitoring in the field of public procurement, identify problems in law enforcement and areas for improvement. Results: it has been determined that legal regulation of control and monitoring in the field of public procurement reveals a number of gaps and conflicts in its regulatory and legal acts, partly due to their fragmentary nature and inconsistency with modern challenges, which negatively affects law enforcement practice and the effectiveness of control measures in this area. The need for a clear division of functions and powers between control bodies, improvement of control and monitoring mechanisms, and expansion of the use of digital procurement analysis tools has been proven. Directions for harmonising national legislation with European standards in the field of public procurement have been identified. Discussion: it has been established that the current model of legal regulation of control and monitoring in the field of public procurement does not fully ensure the achievement of its main goal – the prevention of violations and the effective use of public funds; law enforcement practice confirms that the focus of control activities is still shifted towards responding to violations rather than preventing them, therefore, there remains a need to strengthen the preventive function of monitoring and to further improve legislation in this area, which should be aimed at creating a competitive national model based on updated mechanisms for all types of control and monitoring of procurement in Ukraine, and brought closer to EU standards.